2018
DOI: 10.1002/dta.2531
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and elimination of the catechol‐o‐methyltransferase inhibitor tolcapone in the horse

Abstract: The metabolism of the masking agent tolcapone in the horse has been investigated. This substance was found to have undergone various chemical transformations that produced a large variety of phase I metabolites, as well as glucuronide and sulfate conjugation. Confirmation of the presence of tolcapone and the 3‐O‐methylated metabolite in the blood samples collected up to 240 minutes and in urine obtained up to 24 hours, was successfully conducted using both gas chromatography– and liquid chromatography–tandem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…This provided a good basis for further research into 3‐MT and potential dopamine‐related compound misuse. Stanley et al found that tolcapone and its metabolites were readily detected in all samples for up to 18 h post‐administration and the dose administered in this study was thought to be a third or half of what would be used as a masking agent for dopamine‐related doping 139 …”
Section: Applicationsmentioning
confidence: 76%
See 3 more Smart Citations
“…This provided a good basis for further research into 3‐MT and potential dopamine‐related compound misuse. Stanley et al found that tolcapone and its metabolites were readily detected in all samples for up to 18 h post‐administration and the dose administered in this study was thought to be a third or half of what would be used as a masking agent for dopamine‐related doping 139 …”
Section: Applicationsmentioning
confidence: 76%
“…Dopamine and related compounds are of particular interest due to the stimulant effects on the equine nervous system. 139 It has been proposed that a lack of information on equine metabolism of dopamine-related compounds may permit their abuse to go undetected in current screening efforts. 140 ily detected in all samples for up to 18 h post-administration and the dose administered in this study was thought to be a third or half of what would be used as a masking agent for dopamine-related doping.…”
Section: Equine Anti-dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…T A B L E 1 Proposed nitecapone metabolites detected during LC-MS screening of hydrolysed urine and plasma F I G U R E 4 Bar chart (annotated with the maximum peak area) showing the most abundance metabolites that were detected in postadministration urine pattern observed following both tolcapone 11,12 and entacapone administration. 7 Unlike nitecapone, metabolites with a reduced pentane-2,4-dione side chain (e.g.…”
Section: Resultsmentioning
confidence: 99%